ULAMAS AND HIS INFLUENCE ON CONFLICT RESOLUTION : THE ROLE OF HETEROGENEITY IN COMMUNITIES STRUCTURE - DAVY HENDRI (Maqdis: Jurnal Kajian Ekonomi Islam, 2016)
This paper examines some concepts regarding religion and conflict, more specifically, the role of Islamic religious leaders in the conflict resolution. In many Muslim countries, Islamic religious leaders play significant roles, not only in the religious realm, but also in the social, cultural, and even political realm. In contrast, the social environment will also determine the level of quality of religious leader’s influence in the form of obedience from citizens over the handling of (resolution) social problems in general and specifically conflict. In the heterogeneous socio-economic structure community realizing those are becoming a major challenge. This article examines the relationship between socio-economic structure of the community with the conflict resolution through the role of the local informal leader, in this case religious leaders (ulama). Data analysis was performed using a combination of SUSENAS and PODES provided by BPS, the unit of analysis based communities around 70,000 villages which aggregated at about 480 districts/cities level of 33 provinces in Indonesia in 2011. At initial stage, we creating specific ulama’s quality measurement, named Indek Kualitas Pengaruh Ulama. Then, because of abundance of zero conflict cases and data overdispersion, we analyze this index relation with socio-economic communities structure through ZIP (Zero-Inflated Poisson) regression. This study found that "stable" socio-economic structure of the communities are determine the ulama’s quality. On the one hand, worsening community social cohesion represented by the high polarization index, tend to erode the ulama’s role (influence) especially in resolving conflict. Conversely, a low polarization index, boosted the confidence level (general trust) to the role of ulama.